Diferencias en el grosor del tejido blando facial, en una muestra de población Colombiana, estudio exploratorio (2022)
Craniofacial dimensions and facial soft tissue depths help shape the overall appearance of the face. Little is known about soft tissue dynamics with respect to skeletal malocclusions in relation to sex and age and how these influence facial soft tissue physiognomy. Therefore, the aim of this study is to compare the facial soft tissue thickness of individuals with skeletal class I, II and III malocclusions and to determine the differences according to sex.